Soil microbiomes of reclaimed and abandoned mines of the Yamal region - Pershina, Elizaveta; Ivanova, Ekaterina; Kimeklis, Anastasia; Zverev, Alexey; Kichko, Arina; Aksenova, Tatiana; Andronov, Evgeny; Abakumov, Evgeny (Polish Polar Research, 2020)
Here we investigate the microbiomes of the soil samples from the Yamal Peninsula (the surroundings of Salekhard city, Russian Federation) using a high-throughput sequencing approach. The main goal was to investigate the impact of mining on soils within the following regeneration, both during the reclamation practice and natural self-growth. Several quarries were studied, engaged in sand, clay and chromatic ores mining. The taxonomic analysis of the soil microbiomes revealed 50 bacterial and archaeal phyla; among the dominant phyla were: Proteobacteria, Actinobacteria, Acidobacteria, Chroloflexi, Gemmatimonadetes, Verrucomicrobia, Planctomycetes, Bacteroidetes, AD3, and Nitrospirae. Compared to the typical tundra soil, which was chosen as a control, the disturbed soils had increased biodiversity and total counts for soil bacteria, archaea, and fungi, especially in the cryosolic horizon. The different mining strategies caused significantly different transformations of soil microbiomes, which was less pronounced for self-growth compared to reclaimed quarries. This isolation of the reclaimed quarry was mainly associated with the increase of the amount of acidobacteria (fam. Koribacteraceae and Acidobacteriaceae and order Ellin6513), some proteobacterial taxa (fam. Syntrophobacteraceae), and Chloroflexi (fam. Thermogemmatisporaceae). The study also revealed bacteria, which tend to be specific for marine tundra environments: gemmatimonadetes from the order N1423WL and Chloroflexi bacteria from the order Gitt-GS-136.